Notes on the larval morphology of Trichoferus campestris (Coleoptera, Cerambycidae), a wood borer frequently intercepted in wood packaging material. (4th July 2020) - Connell, J.; Hinterstoisser, W.; Hoch, G.
Abstract : Trichoferus campestris (Coleoptera, Cerambycidae) is one of the most frequently intercepted woodborers in imported wood packaging material. Typically, inspectors encounter the insect in the larval stage. Based on analysis of larvae from a total of seven interceptions during import inspections in Austria and comparison with literature, the authors provide an illustrated description of the larval morphology of T. campestris to assist determination of this species. Notes sur la morphologie des larves de Trichoferus campestris (Coleoptera, Cerambycidae), un foreur du bois fréquemment intercepté dans les matériaux d'emballage en bois: Trichoferus campestris (Coleoptera, Cerambycidae) est l'un des foreurs du bois les plus fréquemment interceptés dans les matériaux d'emballage en bois importés. En général, les inspecteurs trouvent cet insecte au stade larvaire. Sur la base de l'analyse des larves provenant d'un total de sept interceptions lors d'inspections à l'importation en Autriche et d'une comparaison avec la littérature scientifique existante, les auteurs fournissent une description illustrée de la morphologie des larves de T. campestris afin d'aider à l'identification de cette espèce. Заметки о морфологии личинок Trichoferus campestris (Coleoptera, Cerambycidae), стволового вредителя, часто выявляемого в древесном упаковочном материале: Trichoferus campestris (Coleoptera, Cerambycidae) является одним из наиболее часто выявляемых в древесном упаковочном материале стволовых вредителей. Как правило, инспекторы обнаруживают насекомое на личиночной стадии. Для помощи в определении этого вида авторы приводят иллюстрированное описание морфологии личинок T. campestris, подготовленное на основе анализа личинок из семи выявлений при проведении досмотра импортного материала в Австрии, а также сравнения с литературными данными.